Democratizar la ciencia desde el arte: el valor del Bioarte para la tecnoética - Ddo. Juan Alberto VICH ÁLVAREZ (Fonseca, Journal of Communication, 2023)
The consequences derived from the scientific-technological practices developed in recent centuries —many of them harmful, even irreversible— are well known; in order to try to solve them, formulas for interdisciplinary dialogue are being sought to reconcile and connect science with politics.